2021
DOI: 10.31681/jetol.936827
|View full text |Cite
|
Sign up to set email alerts
|

Online language learning in times of crisis: Hindrance or opportunity?

Abstract: The COVID-19 pandemic has brought many changes to the way teachers teach and students learn. Although there is a surplus of research on online education, the transition period to online education is also worth investigating. This study set out to explore language learners' perceptions of how they were impacted by emergency remote teaching (ERT). All the participants were students attending an English medium university in Turkey. The mode of teaching, changes in teacher-student and studentstudent interaction, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…There are also negative aspects such as technical problems, less participation in class, lack of course material, low motivation, difficulty of classroom management and measurement and evaluation problem. In this context, considering the existence of both positive and negative aspects of distance education, this result is similar to other studies (Ozkose, Ari, Cakir, 2013;Ozbay, 2015;Baris & Cetinkaya, 2016;Paydar & Dogan, 2019;Gungor, Cangal & Demir, 2020;Karakus et al 2020;Kaya, 2020;Erzen & Ceylan, 2020;Er Turkuresin, 2020;Sumardi & Nugrahani, 2020;Balbay & Erkan, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…There are also negative aspects such as technical problems, less participation in class, lack of course material, low motivation, difficulty of classroom management and measurement and evaluation problem. In this context, considering the existence of both positive and negative aspects of distance education, this result is similar to other studies (Ozkose, Ari, Cakir, 2013;Ozbay, 2015;Baris & Cetinkaya, 2016;Paydar & Dogan, 2019;Gungor, Cangal & Demir, 2020;Karakus et al 2020;Kaya, 2020;Erzen & Ceylan, 2020;Er Turkuresin, 2020;Sumardi & Nugrahani, 2020;Balbay & Erkan, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…On the whole, our study suggests that learners show flexibility to handle unfortunate circumstances in their learning environment as long as they are motivated to successfully complete their programme (in our case in order to start their undergraduate programme), and they appreciate attempts of their teachers that help them achieve their academic aim (cf. Balbay & Erkan, 2021;Erarslan, 2021). This may explain the somehow surprising result of this study that a remarkable number of students saw their speaking skills improved throughout the course even though it has been suggested that ERT favours the learning of reading and writing at the expense of speaking (Öztürk-Karataş & Tuncer, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…The importance that the learners attached to the role of the teachers is indirectly confirmed in the teachers' reports on how they addressed challenges posed by ERT. In other words, the instructional practise planned and realised by the teacher appears to be the main factor to overcome the challenges of ERT (Balbay & Erkan, 2021) and contributing to the teachers' professional satisfaction (MacIntyre et al, 2020). Those practices, including the design of individual and collaborative assignments that engaged learners in online research, selecting videoconferencing tools different from the institutionally provided platform, online feedback, conducting shorter lessons in which screen sharing is reduced to create a classroom atmosphere or allowing learners to select topics to be covered in classes, exemplify how teachers address challenges created in their specific context displaying "an ecology of contextual agency where the development of teacher agency is incorporated into the evolution of the environment and its relative factors" (Chen, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations